Physical attributes of kaolinitic and oxidic oxisols resulting from different usage systems - Centurion, José Frederico [UNESP]; Beutler, Amauri Nelson [UNESP]; Souza, Zigomar Menezes de [UNESP] (Brazilian Archives of Biology and Technology, 2004)
A mineralogia da fração argila e os sistemas de uso exercem fundamental importância na estrutura do solo. Assim, objetivou-se avaliar atributos físicos de um Latossolo Vermelho Distrófico, caulinítico (LVd), e, de um Latossolo Vermelho Eutroférrico, oxídico (LVef), sob diferentes sistemas de uso, localizados no município de Jaboticabal (SP), Brasil. Os sistemas de uso foram: cana-de-açúcar; algodão e mata. Foram avaliadas a densidade do solo, porosidade total, macro e microporosidade, nas profundidades de 0,0-0,1, 0,1-0,2, 0,2-0,3, 0,3-0,4 m. O Latossolo caulinítico (LVd) apresentou maior densidade do solo e menor porosidade total, macro e microporosidade. O uso aumentou a densidade do solo na profundidade de 0,0-0,3 m, com efeitos maiores no Latossolo caulinítico, principalmente na profundidade de 0,1-0,2 m na área cultivada com cana-de-açúcar.

The objective of this study was to assess the physical attributes of a kaolinitic oxisol, medium texture (Haplustox) and an oxidic oxisol, clayey (Eutrustox) under different usage systems, localized in the region of Jaboticabal, SP, Brazil. The usage systems were sugarcane, cotton and forest. Parameters such as soil bulk density, total porosity, macro and microporosity at the depths of 0.0-0.1; 0.1-0.2; 0.2-0.3, and 0.3-0.4 m were evaluated. Haplustox showed greater bulk density and smaller total porosity, macro and microporosity. The usage increased the bulk density in 0.0-0.3 m depth, with greater effects on the kaolinitic oxisol, mainly in 0.1-0.2 m depth in the areas cultivated with sugarcane.
Keywords: Sugarcane; Cotton; Forest; Mineralogy; porosity; Bulk density